GEOMETRIC MODELING TECHNOLOGIES IN NANO- AND BIOENGINEERING: ADVANCES AND APPLICATIONS - Yuldashev Salmonxon Iqboljon ugli (Modern American Journals, 2025)
Geometric modeling is a foundational tool in nano- and bioengineering, enabling precise visualization, analysis, and design of complex nanoscale and biological structures. The integration of computational modeling, parametric design, and simulation technologies allows researchers and engineers to explore molecular architectures, cellular geometries, and biomaterial structures with unprecedented accuracy. This study investigates contemporary geometric modeling technologies in nano- and bioengineering, focusing on theoretical principles, computational methods, and practical applications. Following the IMRaD framework, the research combines systematic literature review, software-based modeling case studies, and experimental validation. Results demonstrate that advanced modeling tools, including molecular modeling software, finite element analysis (FEA), and parametric simulation platforms, significantly enhance structural understanding, predictive capability, and design optimization. The discussion addresses methodological approaches, integration challenges, and future prospects, emphasizing the transformative role of geometric modeling in nanotechnology, tissue engineering, and biomaterials design. The conclusion highlights that geometric modeling technologies are indispensable for innovation, precision, and translational applications in nano- and bioengineering fields.
Keywords: Geometric Modeling, Nanoengineering, Bioengineering, Molecular Simulation, Parametric Design, Computational Modeling, Tissue Engineering, Biomaterials.